PENERAPAN PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN PRESTASI BELAJAR PERENCANAAN DAN INSTALASI SISTEM AUDIO VIDEO SISWA KELAS XI ELKA SEMESTER III SMK NEGERI 3 TABANAN TAHUN PELAJARAN 2022/2023 - I Wayan Sukayasa (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
This research was conducted at SMK Negeri 3 Tabanan in Class XI ELKA whose students' learning achievement in Planning and Installation of Audio Video Systems was quite low. The purpose of this classroom action research is to find out whether the application of project-based learning can improve learning achievement in Planning and Installation of Audio Video Systems for class XI ELKA semester III SMK Negeri 3 Tabanan in the 2022/2023 academic year. This classroom action research involved 33 research subjects who were conducted in two cycles through the stages of planning, implementation, observation/observation and reflection. The data collection method is a learning achievement test. The data analysis method is descriptive. The results obtained from this study indicate an increase in the ability of students to follow the learning process from an initial average of 62.45, in cycle I 72.42 and increased to 81.06 in cycle II with an initial learning mastery of 55% in cycle I increased to 73% and in cycle II increased to 100%. The conclusion that can be drawn from these results is that the application of project-based learning in the implementation of the learning process can improve student achievement in the subject of Planning and Installation of Audio Video Systems.